2022
DOI: 10.3389/fsurg.2022.919225
|View full text |Cite
|
Sign up to set email alerts
|

A sophisticated fracture classification system of the proximal femur trochanteric region (AO/OTA-31A) based on 3D-CT images

Abstract: ObjectiveFracture classification evolves dynamically with new and enhanced imaging modalities. This paper aims to introduce a novel hypothesis of a sophisticated fracture classification system for the proximal femur trochanteric region (AO/OTA-31A) based on 3D-CT images and accommodate the clinical requirement of the worldwide outbreak of geriatric hip fractures with large amounts of surgical operations.MethodsIn the current practice of widely preoperative 3D-CT application and cephalomedullary nailing, we att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…CT has been used in trochanteric fractures for assessing the reliability of classification systems [ 10 , 11 ]. In 2016, Sharma et al [ 7 ] reported that 51 patients with AO/OTA 31-A2 pertrochanteric fractures were evaluated using a pre-operative CT scan, and found that AO/OTA 31-A2 pertrochanteric fractures with a lateral wall height of > 1.68 cm and an anterior component of > 2.10 cm in circumference are not likely to sustain a lateral wall fracture when treated with a dynamic hip screw (DHS).…”
Section: Discussionmentioning
confidence: 99%
“…CT has been used in trochanteric fractures for assessing the reliability of classification systems [ 10 , 11 ]. In 2016, Sharma et al [ 7 ] reported that 51 patients with AO/OTA 31-A2 pertrochanteric fractures were evaluated using a pre-operative CT scan, and found that AO/OTA 31-A2 pertrochanteric fractures with a lateral wall height of > 1.68 cm and an anterior component of > 2.10 cm in circumference are not likely to sustain a lateral wall fracture when treated with a dynamic hip screw (DHS).…”
Section: Discussionmentioning
confidence: 99%
“…Unstable fractures, however, can be due to communition or reverse obliquity, which brings translational forces into action responsible for post-operative construct collapse. Current evolving evidence has elaborated the morphological characteristics and fracture line mapping of these intertrochanteric fractures with the help of 3D-computed tomography [ 5 ]. It has helped surgeons gain better insight into the fracture pattern, pre-operative planning, and execution of surgical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it must be said that it is necessary to have computed tomography with 3D reconstructions at the hospital emergency level because it helps to better preoperative classification of intertrochanteric fractures, especially in a selected group of fractures where stability and sidewall integrity, among other things, are difficult to assess [21].…”
mentioning
confidence: 99%